1995
DOI: 10.1051/rnd:19950309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaerobic fungi on glycoside hydrolase and polysaccharide depolymerase activities, in sacco straw degradation and volatile fatty acid concentrations in the rumen of gnotobiotically reared lambs

Abstract: Summary ― Four naturally born lambs were placed in sterile isolators 24 h after birth, before the natural establishment of the cellulolytic microorganisms. At the age of 4 weeks, a cellulolytic bacterial population of approximately 10 a cells g-1 of rumen contents was established by inoculation with a 10-6 dilution of ruminal contents taken from an adult sheep. A pure culture of Neocallimastix frontalis MCH 3 and Piromyces communis FL was inoculated into the rumen 5 months after birth and a stable popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…With straw, their individual cellulolytic activity, as well as that of the mixed fungal population, was less than that of the conventional controls. Interrelationships between fungi and cellulolytic bacteria have been investigated using two animal models (Williams et ai., 1994;Fonty et al, 1995). After 72 h the degradation of the plant tissues was similar to that in conventional controls (Grenet et ai., 1989).…”
Section: Substratessupporting
confidence: 59%
“…With straw, their individual cellulolytic activity, as well as that of the mixed fungal population, was less than that of the conventional controls. Interrelationships between fungi and cellulolytic bacteria have been investigated using two animal models (Williams et ai., 1994;Fonty et al, 1995). After 72 h the degradation of the plant tissues was similar to that in conventional controls (Grenet et ai., 1989).…”
Section: Substratessupporting
confidence: 59%
“…Moreover, thanks to the development of a rhizoidal network they are able to weaken and even disrupt plant tissue which enhances accessibility to digestible structures [114]. Studies carried out with gnotoxenic lambs harbouring or not fungi confirmed their important role in fibre breakdown in the rumen [115].…”
Section: Microbial Communities Involved In Fibre Degradation In the Rmentioning
confidence: 94%
“…Because the average molecular weight of native polysaccharides is determined by their source of origin and cannot be, in most cases, easily degraded, it is necessary to set up a kind of fast, efficient, and convenient method of degrading the native polysaccharides in order to achieve the desired molecular weight (). Chemical treatment, such as acid or alkali hydrolysis ( ), is often used, but its consumption of solvents and energy is vast and chemical wastes are often unavoidable. So, the physical degradation method of polysaccharide is potentially likely.…”
Section: Introductionmentioning
confidence: 99%